PEMANFAATAN SAMPAH KERTAS SEBAGAI BAHAN BAKU PAPERBOARD UNTUK MEMPRODUKSI BENDA FUNGSI DAN ESTETIK - Firman Hawari; Agus Sachari; Adhi Nugraha (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2020)
The direction of the implementation of this study is to reduce dependence on natural resources and preserve them from extinction, especially timber natural resources. Green design content is a systematic implementation in each stage. An initial idea was to find an alternative building material that was environmentally friendly. One of the implementations is conducting experiments on panel production from paper waste materials. Paper panels that have the same capabilities as pre-existing panel products. The aim is to make it an interior design material for building, both for construction and aesthetic functions. The consideration of the selection of panel materials is the wide scope of utilization, flexibility, easy treatment, and factors of people who are used to it. In full, this type of paper waste contains forms that are fatty, limp and fragile. This character strongly supports the implementation of that perception. Furthermore, this character becomes a stimulus to bring up the manufacturing method, which is a vertical cross-configuration, which uses limp and fragile sheet paper and then arranged into a panel area with a thickness of 20 mm which requires hard, sturdy, and strong properties.